Reparative Effects of Dandelion Fermentation Broth on UVB-Induced Skin Inflammation - Zhang Y; Fu H; Zhang Y; Wang D; Zhao D; Zhang J; Li M; Wang C (Dove Medical Press, 2022)
Yuzhi Zhang,1,2 Hao Fu,1,2 Yongtao Zhang,1,2 Dongdong Wang,1,2 Dan Zhao,1- 3 Jiachan Zhang,1- 3 Meng Li,1,2 Changtao Wang1- 3 1Beijing Key Lab of Plant Resource Research and Development, College of Chemistry and Materials Engineering, Beijing Technology and Business University, Beijing, People's Republic of China; 2Institute of Cosmetic Regulatory Science, Beijing Technology and Business University, Beijing, People's Republic of China; 3Beijing Advanced Innovation Center for Food Nutrition and Human Health, Beijing Technology and Business University, Beijing, People's Republic of ChinaCorrespondence: Meng Li; Changtao Wang, Beijing Technology and Business University, Beijing, 100048, People's Republic of China, Tel +86 10-68984917, Fax +86 10-68984917, Email limeng@btbu.edu.cn; wangct@th.btbu.edu.cnObjective: To evaluate the efficacy of the dandelion fermentation broth in repairing UVB-induced skin inflammation.Methods: Detection of active ingredients in dandelion fermentation broth and water extract. The antioxidant capacity of dandelion fermentation broth was investigated by in vitro antioxidant experiments. The influence of the broth on the content of inflammatory factors interleukin-6 (IL-6), interleukin-8 (IL-8) and interleukin-1β (IL-1β), and tumor necrosis factor (TNF-α), in human immortalized epidermal cells (HaCaT) is discussed on the basis of a UVB-induced HaCaT damage model. The effects of the broth on the contents of skin barrier-related proteins kallikrein-7 (KLK-7), filaggrin (FLG) and aquaporin (AQP3) in the UVB-induced damage and repair of the HaCaT mechanism are also comprehensively discussed. The effect of DF on the activation of MAPK pathway proteins was detected by PCR. A chicken embryo chorioallantoic membrane test is used to explore the safety of the dandelion fermentation broth.Results: The results show that the dandelion fermentation broth is rich inTotal sugar, with good free radical scavenging ability and antioxidant effects; it can regulate the MAPK pathway, reduce the expression of inflammatory factors, adjust the skin barrier factors and good safety.Conclusion: Dandelion fermentation broth exhibits repairing effect on UVB-induced skin inflammation.Keywords: dandelion fermentation broth, ultraviolet radiation B, human immortalized epidermal cells, inflammation repair, medicine, daily chemical raw materials